Can the different versions of the Shirom-Melamed Burnout Measure be used to measure burnout among healthcare professionals? A systematic review of psychometric properties - Sabrina Figueiredo; Jacques Arrieux; Samia Abdallah; Timothy C. McCall; Ulrich Koch; Eliezer Oliveira (SpringerOpen, 2024)
Abstract Background The prevalence of Occupational Burnout is high among healthcare professionals (HCP). Hence, it is crucial to have robust measures for ascertaining burnout in this population. The Shirom-Melamed Burnout Measure is a prevalent tool used in the diagnosis of burnout, and in the delivery planning of mental health services. The 14-item Shirom-Melamed Burnout Measure (SMBM) was developed after a methodological revision of the 22-item Shirom-Melamed Burnout Questionnaire (SMBQ). Studies on the psychometric properties of the SMBM and SMBQ exist, but there remains a need for thorough evaluation to assess the methodological quality of individual studies. To address this gap, this systematic review aimed to critically appraise the measurement properties of the different versions of the Shirom-Melamed Burnout Measure/Questionnaire (SMBM/Q) used among healthcare professionals. Methodology Four databases (PubMed, CINAHL, PsychINFO, and Scopus) were searched for studies on the psychometric properties of all versions of the SMBM/Q among HCP. The methodological quality of the studies was evaluated using the COSMIN Risk of Bias checklist. Evidence supporting the measurement properties (EMP) of the SMBM was synthesized using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. Results Our final pool consisted of five research articles. One study on the 12-item SMBM was included to estimate content validity, two studies reported on the 14-item SMBM, while the other two employed the 22-item version. Interestingly, each study used the SMBM in a different language, namely English/Hebrew, Chinese, French, Serbian, and Swedish. Structural validity, internal consistency, and construct validity are the SMBM's most assessed measurement properties. The Hebrew and French versions demonstrated high levels of structural validity and internal consistency, and the remaining reports on validity demonstrated low levels due to methodological flaws. Conclusions Per COSMIN guidelines, the SMBM should not be utilized for clinical purposes due to insufficient content validity, but has promising potential with ongoing research. Engaging critical stakeholders for concept elicitation will ensure the relevance, comprehensiveness, and comprehensibility of the PRO items. Likewise, establishing an MIC will allow capturing change over time, which will benefit longitudinal experimental studies. Plain English summary Occupational burnout is a significant problem among healthcare professionals, and it is crucial to have a reliable tool to measure it. The Shirom-Melamed Burnout Measure (SMBM) is commonly used to diagnose burnout and plan mental health services. Studies on the psychometric properties of the SMBM exist, but there remains a need for thorough evaluation to assess the methodological quality of individual studies. To address this gap, this systematic review critically appraised the measurement properties of the different versions of the Shirom-Melamed Burnout Measure (SMBM) used among healthcare professionals. Our findings indicate that only a few studies have examined the SMBM, and they have used the tool in different languages. Structural validity, internal consistency, and construct validity are the SMBM's most assessed measurement properties. We recommend that more research is needed to assess the content validity of the SMBM. We also suggest that critical stakeholders should be involved in the development of the SMBM to ensure that it is relevant, comprehensive, and understandable.